STRATEGI POLITICAL MARKETING UNTUK PEMILIH PEMULA PADA PEMILIHAN GUBERNUR PROVINSI LAMPUNG 2014 MENGGUNAKAN TEKNIK ANALYTICAL HIERARCHY PROCESS (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
ABSTRACT. Technology has become the center of attention the wider community because the birth of the phenomenon of globalization where a political promotion no longer done traditionally but have used the mass media communication , to promote political party or a political candidate. This research used the theory of marketing mix is a collection of controllable tactical marketing tools combined company to produce the desired response from the target market. The purpose of this study was aimed to develop and recommend strategies prioritize what should the delivery of campaign whether social media, print media, electronic media and outdoor media during the campaign Election 2014. Governor of Lampung Province descriptive method in this research is the approach of AHP (Analytical Hierarchy Process). The research results obtained are some alternative strategy is that when seen from the product of political, the price of political, the promotion of political and media and a political priority is good for outdoor media. More will be of some alternative, is to do with intense and serious marketing activities through other media room.